Reading nonsense : a journey through the writing of Edward Lear - Pendlebury, Kathleen Sarah (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2008)
In this thesis I have addressed some of the problems that have arisen in critical approaches to the nonsense works of Edward Lear from the late nineteenth century. I have entitled it "Reading Nonsense" because my central concern is with how best to apprehend the paradoxes inherent in literary nonsense, which inevitably raises interpretative questions. Because nonsense is a "basic type of communication" whose essence is "unresolved tension between [the] presence and absence of meaning" (Tigges, Anatomy 51), we are called upon either to "make sense of" that which claims to offer up no meaning or to surrender ourselves to meaninglessness. Broadly, critical approaches to nonsense fall into two classes: those that maintain that nonsense is not, in fact, "not sense" , but rather a kind of symbolic language that can be reconciled into meaning; and those which uphold the nonsensicality of nonsense, maintaining that certain ambiguities and paradoxes cannot be accounted for, and it is inappropriate to try to do so. In addition, Lear's texts are situated in various traditions of writing for children and adults and in the distinctive setting of the Victorian era; and these cultural and literary influences play an important role in the interpretation and misinterpretation of nonsense. My first chapter comprises a mise en scène of the genre of literary nonsense; while in Chapter 2 I turn to the cultural backdrop of Lear's nonsense in particular, and examine one of the claims frequently made in nonsense criticism: that Lear's literary nonsense is distinctively "Victorian" . Chapter 3, "How to Read a Learian Limerick" , rests on the exegesis of nonsense that appears in Chapter 1, for here I propose a technique for reading Lear's limericks that preserves both their "sensical" and nonsensical elements in contrast to critical analyses that attempt to reconcile the nonsense into a code. In Chapter 4 I examine Lear's songs from the critical perspectives of nonsense and of romanticism. Finally, in conclusion, I consider the role and significance of humour in nonsense, and gesture towards further possible explorations, including in the appendix my essay on the nonsense poetry of South African writer Philip de Vos.
Keywords: Lear, Edward, 1812-1888; Lear, Edward, 1812-1888 -- Criticism and interpretation; English poetry -- 19th century -- Criticism and interpretation